Three-dimensional study of stack on the performance of the proton exchange membrane fuel cell. (15th February 2019) - Lim, B.H.; Majlan, E.H.; Daud, W.R.W.; Rosli, M.I.; Husaini, T.
Abstract: The distribution of reactant in the proton exchange membrane fuel cell (PEMFC) is crucial because the performance of the fuel cell is determined by the lowest performance cell. The reactant is distributed from the manifold to the cells in the stack and further distributed into the flow field channels (depending on the flow field design). The three-dimensional PEMFC is comparatively studied as a dual-cell, a quad-cell and a hexa-cell stack. The previously investigated modified parallel flow field is used as the anode flow field. The dual-, quad- and hexa-cell stacks are connected in series to study the effect of PEMFC performance when the number of cells increases in a PEMFC stack. Computational fluid dynamics (CFD) is used to study the current density generation of a PEMFC stack. The results demonstrate that when the quantity of cells rises in a stack, the current density decreases. Six equations are formed at different cell potentials to predict the PEMFC performance as the quantity of cells increases. Highlights: Effect on quantity of cells in a performance of a PEMFC stack is investigated. Predict the performance of a PEMFC as the number of cells in a stack change. A set of novel equations is proposed.